A preparation method of nano silicon dioxide for rubber

Nanosilica was prepared by acidification and hydrolysis and subjected to porous structure and superhydrophobic modification, which solved the dispersion stability of nanosilica in rubber, significantly improving the comprehensive performance and wear resistance of rubber.

CN118185128BActive Publication Date: 2025-02-18SHANDONG YINJING NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410448552.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-15
Publication Date
2025-02-18
Estimated Expiration
2044-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively disperse and stabilize nanosilicon dioxide in rubber, resulting in limited improvement in the overall performance of rubber and contamination problems.

Method used

Nanosilica sols were prepared by acidification and hydrolysis, and porous nanosilica was formed by precoating of polyvinylpyrrolidone and etching of sodium hydroxide. Then, modifiers such as dodecyltriethoxysilane and cocamide are used for superhydrophobic modification to improve its dispersion stability in the rubber.

Benefits of technology

It significantly improves the mechanical properties and wear resistance of rubber, improves the dispersion stability of nano-silica, reduces pollution, and achieves the comprehensive performance improvement of rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118185128B_ABST
    Figure CN118185128B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing nano silicon dioxide for rubber, and belongs to the technical field of silica sol materials. First, the invention pre-treats the prepared silica sol particles, and then uses dodecyl triethoxysilane DTES and cocamide DEA to mix and modify them in equal proportions. Dodecyl triethoxysilane DTES and cocamide DEA show obvious synergistic effects, and can achieve efficient super-hydrophobic modification of the silicon dioxide surface. In subsequent mixing, the dispersion stability of silicon dioxide in the rubber system can be effectively improved, and the binding property of rubber and inorganic particles can be improved, thereby improving the mechanical properties and comprehensive properties of the rubber, such as wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silica sol materials, and specifically relates to a method for preparing nano silicon dioxide for rubber. Background Art

[0002] Rubber, especially rubber used in the preparation of automobile tires, must be filled with reinforcing agents to improve the physical and mechanical properties of its vulcanized rubber in order to meet the use requirements of vulcanized rubber products. Among rubber reinforcing agents, carbon black is the most important reinforcing agent with the most significant reinforcing effect and the largest amount of reinforcing agent, followed by precipitated silica. The dust of reinforcing agents, especially carbon black, causes serious black pollution to the production environment and the surrounding environment. Silica is a silica powder, which is an inorganic nanopowder. It has a high specific surface energy and many hydroxyl groups on the surface of the particles. It has poor compatibility with rubber. It is difficult to evenly disperse it in the rubber matrix by mechanical shearing, and it exists in the form of agglomerates with larger particle sizes. The positive effect of adding carbon black and silica at the same time is mainly to improve the strength performance of rubber, and there is no obvious improvement on other properties of rubber.

[0003] To solve the problem of dispersibility of silica, CN108946745A discloses a modified precipitated silica and a preparation method thereof, wherein the preparation method comprises first adding a cationic surfactant to a water glass solution, heating the solution to obtain a solution A, then adding sodium sulfate to the solution A for precipitation reaction, adjusting the pH with a sulfuric acid solution during the reaction, and aging the solution after the reaction is completed to obtain the modified precipitated silica. In this method, a cationic surfactant is added to the water glass solution, and the cationic surfactant carries a positive charge after being dissolved in water. The negative charge on the surface of the precipitated silica will interact with the cation to achieve the effect of coating modification, but the dispersion effect modification in rubber is limited, and the improvement of the performance of the rubber itself is also very limited.

[0004] CN111073042A discloses a method for preparing ultra-dispersed nano-silica for rubber filler, wherein firstly, alkylphenol polyoxyethylene ether and silane coupling agent are copolymerized, and the generated product, organic silicon / alkylphenol polyoxyethylene ether copolymer, is used to perform multi-point anchoring modification on the surface of nano-silica particles, and then polar pre-emulsification treatment is performed using unsaturated acrylate polar monomers and aryl vinyl monomers, and then ultra-dispersed nano-silica is prepared by in-situ polymerization. The nano-silica finished product is directly modified, and the modified dispersion effect is limited. Moreover, more organic matter is used in the modification process, and the wastewater generated is difficult to treat.

[0005] Therefore, how to improve the dispersion stability of silica and significantly enhance the comprehensive performance of rubber materials while reducing pollution is a technical problem that needs to be solved urgently. Summary of the invention

[0006] The present invention aims at the problems existing in the prior art and provides a nano silicon dioxide which is added into rubber for mixing, and various properties of the obtained rubber are significantly improved.

[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0008] A method for preparing nano silicon dioxide for rubber, comprising the following preparation steps:

[0009] (1) Preparation of nano-silica sol: Using the acid hydrolysis method, ethanol, TEOS, and deionized water are added to a beaker in sequence, and magnetically stirred for 2-4 hours in a water bath at 50-60°C to fully mix them. After the solution is cooled to room temperature, hydrochloric acid is added, and magnetic stirring is continued at room temperature for 24-36 hours. Ethyl silicate undergoes hydrolysis reaction under acidic conditions to form nano-silica sol;

[0010] (2) Silica sol pretreatment: adding polyvinyl pyrrolidone to the nano-silica sol obtained in step (1) at a molar ratio of (3-5):1, heating in a water bath to 80-90°C with continuous stirring, maintaining the constant temperature for 1-2 hours, and cooling naturally to obtain a mixed sol; adding sodium hydroxide solution at a volume ratio of 1:10, heating to 40-50°C and maintaining for 30-40 minutes, cooling naturally and freeze-drying to obtain porous nano-silica;

[0011] (3) Super hydrophobic modification of porous nano-silica: Take porous nano-silica, add ethanol and water and mix evenly, adjust the pH to 9-10, add a modifier, increase the temperature and continue the reaction, wash the product three times with anhydrous ethanol by centrifugation to remove residual modifier and impurities, and finally put the product into a vacuum oven and vacuum dry it at 80-100°C for 12-20h to obtain the final product silica.

[0012] Preferably, the volume ratio of ethanol, TEOS, deionized water and hydrochloric acid in step (1) is 28:20:7:0.8.

[0013] More preferably, instead of the method of preparing silica sol by acidification and hydrolysis in step (1) of the present invention, commercially available nano silica sol products can be used for subsequent process steps. The commercially available products are not limited to the type of silica sol, and acidic, alkaline and neutral silica sol products are all acceptable.

[0014] Preferably, the molar concentration of the sodium hydroxide solution in step (2) is 2-3 mol / L.

[0015] Preferably, in step (3), the mass ratio of the porous nano-silica, ethanol and water is 1:15:3, and the mass ratio of the modifier to the porous nano-silica is 0.5:1.

[0016] Preferably, the modifier in step (3) is obtained by mixing dodecyltriethoxysilane DTES and cocamide DEA in a mass ratio of 1:1.

[0017] Preferably, the heating temperature in step (3) is 50-60° C. and the reaction time is 1-2 h.

[0018] Preferably, in step (3), sodium hydroxide or aqueous ammonia can be used to adjust the pH.

[0019] The nano silicon dioxide prepared by the present invention is applied to rubber materials. The specific use method is as follows: natural rubber is plasticized in an internal mixer for 3 minutes, zinc oxide, stearic acid, antioxidant, and accelerator are added in sequence, and mixed for 3 minutes; nano silicon dioxide is added, and mixed for 3 minutes; sulfur is added, and mixed for 3 minutes; the mixed rubber is taken out. The mixed rubber is mixed on an open mixer for 3 minutes, thinned 5 times, and sliced, and parked for 24 hours. The mass ratio of natural rubber, zinc oxide, stearic acid, antioxidant, accelerator, sulfur, and nano silicon dioxide is 100:5:0.5:2:2.2:1:30.

[0020] Beneficial Effects

[0021] (1) First, the present invention pre-treats the prepared silica sol particles by coating them with a layer of high molecular weight polymer. Under the protection of the high molecular weight polymer, the silica particles are etched with sodium hydroxide to form silica sol particles with a rough and porous surface, which is more conducive to orderly grafting modification. At the same time, during the mixing process, the combination with the organic colloid is more firmly achieved.

[0022] (2) Subsequently, dodecyl triethoxysilane DTES and cocamide DEA are mixed in equal proportions for modification. After the ethoxy group of dodecyl triethoxysilane is hydrolyzed, it can react with the silanol group on the surface of silica sol and be grafted on the surface of silica, thereby improving the dispersion stability of silica. Adding an appropriate amount of amphiphilic cocamide DEA can help dodecyl triethoxysilane and silica particles to be evenly dispersed in the system, thereby improving the modification effect. After dodecyl triethoxysilane DTES and cocamide DEA are mixed in equal proportions, an obvious synergistic effect is exhibited, which can achieve efficient super-hydrophobic modification of the silica surface. In the subsequent mixing, the dispersion stability of silica in the rubber system can be effectively improved, and the binding property of rubber and inorganic particles can be improved, thereby improving the mechanical properties and wear resistance of the rubber and other comprehensive properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the surface contact angle of silicon dioxide obtained in Example 3 of the present invention;

[0024] Figure 2 The SEM and TEM images of the silicon dioxide obtained in Example 3 of the present invention, wherein A is the SEM image and B is the TEM image;

[0025] Figure 3 The wear resistance data of Examples 1-3 and Comparative Examples 1-5 are shown in FIG. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0027] Example 1

[0028] A method for preparing nano silicon dioxide for rubber, comprising the following preparation steps:

[0029] (1) Preparation of nano-silica sol: Using the acid hydrolysis method, ethanol, TEOS, and deionized water were added to a beaker in sequence, and magnetically stirred for 2 h in a water bath at 50-60°C to fully mix them. After the solution was cooled to room temperature, hydrochloric acid was added, and magnetic stirring was continued at room temperature for 24 h. Ethyl silicate was hydrolyzed under acidic conditions to form nano-silica sol;

[0030] (2) Silica sol pretreatment: adding polyvinyl pyrrolidone to the nano-silica sol obtained in step (1) at a molar ratio of 3:1, heating in a water bath to 80-90°C with continuous stirring, maintaining the constant temperature for 1 hour, and cooling naturally to obtain a mixed sol; adding sodium hydroxide solution at a volume ratio of 1:10, heating to 40-50°C and maintaining for 30 minutes, cooling naturally, and freeze-drying to obtain porous nano-silica;

[0031] (3) Super-hydrophobic modification of porous nano-silica: Take porous nano-silica, add ethanol and water, mix evenly, adjust the pH to 9-10, add a modifier, increase the temperature and continue the reaction, wash the product three times with anhydrous ethanol by centrifugation to remove residual modifier and impurities, and finally put the product into a vacuum oven and vacuum dry it at 80-100°C for 12 hours to obtain the final product silica.

[0032] The volume ratio of ethanol, TEOS, deionized water and hydrochloric acid in step (1) is 28:20:7:0.8.

[0033] The molar concentration of the sodium hydroxide solution in step (2) is 2 mol / L.

[0034] In step (3), the mass ratio of ethanol and water added to the porous nano-silica is 1:15:3, and the mass ratio of the modifier to the porous nano-silica is 0.5:1.

[0035] The modifier in step (3) is obtained by mixing dodecyl triethoxysilane DTES and cocamide DEA in a mass ratio of 1:1.

[0036] The heating temperature of step (3) is 50-60°C and the reaction time is 1h.

[0037] In step (3), sodium hydroxide or aqueous ammonia can be used to adjust the pH.

[0038] The nano silicon dioxide prepared in this embodiment is applied to rubber materials. The specific method of use is as follows: the natural rubber is plasticized in an internal mixer for 3 minutes, zinc oxide, stearic acid, antioxidant, and accelerator are added in sequence, and mixed for 3 minutes; nano silicon dioxide is added, and mixed for 3 minutes; sulfur is added, and mixed for 3 minutes; the mixed rubber is taken out. The mixed rubber is mixed on an open mixer for 3 minutes, thinned 5 times, and sliced ​​and parked for 24 hours. The mass ratio of natural rubber, zinc oxide, stearic acid, antioxidant, accelerator, sulfur, and nano silicon dioxide is 100:5:0.5:2:2.2:1:30.

[0039] Example 2

[0040] A method for preparing nano silicon dioxide for rubber, comprising the following preparation steps:

[0041] (1) Preparation of nano-silica sol: Using the acid hydrolysis method, ethanol, TEOS, and deionized water were added to a beaker in sequence, and magnetically stirred for 3 h in a water bath at 50-60°C to fully mix them. After the solution was cooled to room temperature, hydrochloric acid was added, and magnetic stirring was continued for 30 h at room temperature. Ethyl silicate was hydrolyzed under acidic conditions to form nano-silica sol;

[0042] (2) Silica sol pretreatment: adding polyvinyl pyrrolidone to the nano-silica sol obtained in step (1) at a molar ratio of 4:1, heating in a water bath to 80-90°C with continuous stirring, maintaining the constant temperature for 1.5 hours, and cooling naturally to obtain a mixed sol; adding sodium hydroxide solution at a volume ratio of 1:10, heating to 40-50°C and maintaining for 30 minutes, cooling naturally, and freeze-drying to obtain porous nano-silica;

[0043] (3) Super-hydrophobic modification of porous nano-silica: Take porous nano-silica, add ethanol and water, mix evenly, adjust the pH to 9-10, add a modifier, increase the temperature and continue the reaction, wash the product three times with anhydrous ethanol by centrifugation to remove residual modifier and impurities, and finally put the product into a vacuum oven and vacuum dry it at 80-100°C for 15h to obtain the final product silica.

[0044] The volume ratio of ethanol, TEOS, deionized water and hydrochloric acid in step (1) is 28:20:7:0.8.

[0045] The molar concentration of the sodium hydroxide solution in step (2) is 3 mol / L.

[0046] In step (3), the mass ratio of ethanol and water added to the porous nano-silica is 1:15:3, and the mass ratio of the modifier to the porous nano-silica is 0.5:1.

[0047] The modifier in step (3) is obtained by mixing dodecyl triethoxysilane DTES and cocamide DEA in a mass ratio of 1:1.

[0048] The heating temperature of step (3) is 50-60°C and the reaction time is 1h.

[0049] In step (3), sodium hydroxide or aqueous ammonia can be used to adjust the pH.

[0050] The nano silicon dioxide prepared in this embodiment is applied to rubber materials. The specific method of use is as follows: the natural rubber is plasticized in an internal mixer for 3 minutes, zinc oxide, stearic acid, antioxidant, and accelerator are added in sequence, and mixed for 3 minutes; nano silicon dioxide is added, and mixed for 3 minutes; sulfur is added, and mixed for 3 minutes; the mixed rubber is taken out. The mixed rubber is mixed on an open mixer for 3 minutes, thinned 5 times, and sliced ​​and parked for 24 hours. The mass ratio of natural rubber, zinc oxide, stearic acid, antioxidant, accelerator, sulfur, and nano silicon dioxide is 100:5:0.5:2:2.2:1:30.

[0051] Example 3

[0052] A method for preparing nano silicon dioxide for rubber, comprising the following preparation steps:

[0053] (1) Preparation of nano-silica sol: Using the acid hydrolysis method, ethanol, TEOS, and deionized water were added to a beaker in sequence, and magnetically stirred for 4 h in a water bath at 50-60°C to fully mix the mixture. After the solution was cooled to room temperature, hydrochloric acid was added, and magnetic stirring was continued for 36 h at room temperature. Ethyl silicate was hydrolyzed under acidic conditions to form nano-silica sol.

[0054] (2) Silica sol pretreatment: polyvinyl pyrrolidone was added to the nano-silica sol obtained in step (1) at a molar ratio of 5:1, heated in a water bath to 80-90°C with continuous stirring, maintained at a constant temperature for 2 hours, and cooled naturally to obtain a mixed sol; sodium hydroxide solution was added at a volume ratio of 1:10, heated to 40-50°C and maintained for 40 minutes, cooled naturally, and freeze-dried to obtain porous nano-silica;

[0055] (3) Super hydrophobic modification of porous nano-silica: Take porous nano-silica, add ethanol and water, mix evenly, adjust the pH to 9-10, add a modifier, increase the temperature and continue the reaction, wash the product three times with anhydrous ethanol by centrifugation to remove residual modifier and impurities, and finally put the product into a vacuum oven and vacuum dry it at 80-100°C for 20 hours to obtain the final product silica.

[0056] The volume ratio of ethanol, TEOS, deionized water and hydrochloric acid in step (1) is 28:20:7:0.8.

[0057] The molar concentration of the sodium hydroxide solution in step (2) is 3 mol / L.

[0058] In step (3), the mass ratio of ethanol and water added to the porous nano-silica is 1:15:3, and the mass ratio of the modifier to the porous nano-silica is 0.5:1.

[0059] The modifier in step (3) is obtained by mixing dodecyl triethoxysilane DTES and cocamide DEA in a mass ratio of 1:1.

[0060] The heating temperature of step (3) is 50-60°C and the reaction time is 2h.

[0061] In step (3), sodium hydroxide or aqueous ammonia can be used to adjust the pH.

[0062] The nano silicon dioxide prepared in this embodiment is applied to rubber materials. The specific method of use is as follows: the natural rubber is plasticized in an internal mixer for 3 minutes, zinc oxide, stearic acid, antioxidant, and accelerator are added in sequence, and mixed for 3 minutes; nano silicon dioxide is added, and mixed for 3 minutes; sulfur is added, and mixed for 3 minutes; the mixed rubber is taken out. The mixed rubber is mixed on an open mixer for 3 minutes, thinned 5 times, and sliced ​​and parked for 24 hours. The mass ratio of natural rubber, zinc oxide, stearic acid, antioxidant, accelerator, sulfur, and nano silicon dioxide is 100:5:0.5:2:2.2:1:30.

[0063] Comparative Example 1

[0064] The preparation method of this comparative example is the same as that of Example 3 except that the silica sol is not pretreated. That is:

[0065] A method for preparing nano silicon dioxide for rubber, comprising the following preparation steps:

[0066] (1) Preparation of nano-silica: Using the acid hydrolysis method, ethanol, TEOS, and deionized water were added to a beaker in sequence, and magnetically stirred in a water bath at 50-60°C for 4 hours to fully mix them. After the solution was cooled to room temperature, hydrochloric acid was added, and magnetic stirring was continued at room temperature for 36 hours. Ethyl silicate was hydrolyzed under acidic conditions to form nano-silica sol, which was then freeze-dried to obtain nano-silica;

[0067] (2) Super hydrophobic modification of silica: Take nano-silica, add ethanol and water and mix evenly, adjust the pH to 9-10, add a modifier, increase the temperature and continue the reaction, wash the product three times with anhydrous ethanol by centrifugation to remove the residual modifier and impurities, and finally put the product into a vacuum oven and vacuum dry it at 80-100°C for 20 hours to obtain the final product silica.

[0068] Comparative Example 2

[0069] In this comparative example, except that only dodecyltriethoxysilane DTES is used as the modifier, the other raw materials and steps are the same as those in Example 3.

[0070] That is, the modifier in step (3) is dodecyltriethoxysilane DTES.

[0071] Comparative Example 3

[0072] In this comparative example, except for changing the composition of the modifier, the rest of the raw materials and steps are the same as those in Example 3.

[0073] The modifier in step (3) is obtained by mixing dodecyl triethoxysilane DTES and cocamide DEA in a mass ratio of 2:1.

[0074] Comparative Example 4

[0075] In this comparative example, except for changing the composition of the modifier, the rest of the raw materials and steps are the same as those in Example 3.

[0076] The modifier in step (3) is obtained by mixing dodecyl triethoxysilane DTES and cocamide DEA in a mass ratio of 1:2.

[0077] Comparative Example 5

[0078] Use white carbon black to replace the silicon dioxide in Example 3 of the present invention to prepare the film: plasticize the natural rubber in an internal mixer for 3 minutes, add zinc oxide, stearic acid, antioxidant, and accelerator in sequence, and mix for 3 minutes; add white carbon black and mix for 3 minutes; add sulfur and mix for 3 minutes; take out the mixed rubber. Mix the mixed rubber on the open mixer for 3 minutes, pass it through 5 times, take out the sheet, and park it for 24 hours. The mass ratio of natural rubber, zinc oxide, stearic acid, antioxidant, accelerator, sulfur, and white carbon black is 100:5:0.5:2:2.2:1:30.

[0079] Performance Testing

[0080] Silicon dioxide was prepared according to the method of the embodiment and the comparative example, and a film was prepared according to the method of the embodiment and the comparative example. After the film was parked, it was vulcanized on a flat vulcanizer to prepare a test piece, and the vulcanization conditions were 160°C / 10MPa×15min.

[0081] Test Method

[0082] Surface contact angle characterization: The silica powder sample was first pressed into tablets with a pressure of 500 MPa and a constant pressure of 30 min. A surface contact angle tester (Dataphysics, Germany, OCA40Micro) was used to perform contact angle tests to characterize the wetting properties of the sample. The measurements were performed at room temperature, and 4 μL of water was added to the probe each time.

[0083] Scanning electron microscopy characterization:

[0084] The samples were adhered to a conductive tape and treated with gold spraying for 3 min in a vacuum coater before testing. Field emission scanning electron microscopy (Merlin, Zeiss, Germany) was used to characterize and analyze the samples at an accelerating voltage of 10 kV.

[0085] Transmission electron microscopy characterization:

[0086] The morphology of the samples was characterized by a JEOL JEM-2010 transmission electron microscope.

[0087] Mechanical properties:

[0088] The test was carried out in accordance with GB / T528-2009.

[0089] Wear resistance:

[0090] The test was carried out using an Akron abrasion testing machine in accordance with GB / T1689-2014.

[0091] Table 1 Performance test results

[0092]

[0093] From the experimental data of the present invention, we can see that the silica obtained in the embodiment of the present invention exhibits super hydrophobicity, and the mechanical properties of the obtained film are significantly improved. At the same time, the dispersion stability of silica is improved, and the overall wear resistance of the rubber matrix is ​​improved as a whole (such as Figure 3 ). In comparative example 1, there is no pre-packaging of the polymer and the etching effect of sodium hydroxide, the subsequent modification effect decreases, and the binding force with the rubber decreases, thereby causing the weakening of the comprehensive performance of the film. In comparative examples 2-7, the synergistic balance between dodecyl triethoxysilane DTES and cocamide DEA is broken, and the hydrophobic modification effect decreases, thereby causing the dispersion stability of silicon dioxide to weaken, and thus the film performance also shows varying degrees of weakening. The present invention is a key technical means for realizing its super-hydrophobic treatment for the pretreatment of nano silicon dioxide and the subsequent modification treatment, and the lack of one is weak.

[0094] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A method for preparing nano-silicon dioxide for rubber, characterized in that: The method comprises the following preparation steps: (1) Preparation of nano-silica sol: Using the acid hydrolysis method, ethanol, TEOS, and deionized water are added to a beaker in sequence, and magnetically stirred for 2-4 hours in a water bath at 50-60°C to fully mix them. After the solution is cooled to room temperature, hydrochloric acid is added, and magnetic stirring is continued at room temperature for 24-36 hours. Ethyl silicate undergoes hydrolysis reaction under acidic conditions to form nano-silica sol; (2) Silica sol pretreatment: adding polyvinyl pyrrolidone to the nano-silica sol obtained in step (1) at a molar ratio of (3-5):1, heating in a water bath to 80-90°C with continuous stirring, maintaining the constant temperature for 1-2 hours, and cooling naturally to obtain a mixed sol; adding sodium hydroxide solution at a volume ratio of 1:10, heating to 40-50°C and maintaining for 30-40 minutes, cooling naturally, and freeze-drying to obtain porous nano-silica; (3) Super hydrophobic modification of porous nano-silica: Take porous nano-silica, add ethanol and water, mix evenly, adjust the pH to 9-10, add a modifier, heat and continue the reaction, the product is washed three times by centrifugation with anhydrous ethanol to remove the residual modifier and impurities, and finally put the product into a vacuum oven and vacuum dry it at 80-100° C. for 12-20 hours to obtain the final product silica; The volume ratio of ethanol, TEOS, deionized water and hydrochloric acid in step (1) is 28:20:7:0.8; The molar concentration of the sodium hydroxide solution in step (2) is 2-3 mol / L; In step (3), the mass ratio of the porous nano-silica, ethanol and water is 1:15:3, and the mass ratio of the modifier to the porous nano-silica is 0.5:1; The modifier in step (3) is obtained by mixing dodecyl triethoxysilane DTES and cocamide DEA in a mass ratio of 1:

1.

2. The method for preparing nano silicon dioxide for rubber according to claim 1, characterized in that: The heating temperature in step (3) is 50-60°C and the reaction time is 1-2h.

Citation Information

Patent Citations

  • Modified precipitated silicon dioxide and preparation method for modified precipitated silicon dioxide

    CN108946745A

  • Preparation method of ultra-dispersed nano white carbon black for rubber filler

    CN111073042A